How Rome fell : death of a superpower - Goldsworthy, Adrian Keith (New Haven : Yale University Press, 2009)
The author discusses how the Roman Empire--an empire without a serious rival--rotted from within, its rulers and institutions putting short-term ambition and personal survival over the wider good of the state.
Pt. 1. Crisis? The third century. The kingdom of gold -- The secret of empire -- Imperial women -- King of kings -- Barbarians -- The queen and the 'necessary' emperor -- Crisis -- Pt. 2. Recovery? The fourth century. The four--Diocletian and the tetrarchy -- The Christian -- Rivals -- Enemies -- The pagan -- Goths -- East and west -- Pt. 3. Fall? The fifth and sixth centuries. Barbarians and Romans : generals and rebels -- The sister and the eternal city -- The Hun -- Sunset on an outpost of empire -- Emperors, kings and warlords -- West and east -- Rise and fall.
Includes bibliographical references (p. 449-465) and index.
Keywords: Rome -- History -- Empire, 284-476.